2016
DOI: 10.1080/07352689.2016.1148980
|View full text |Cite
|
Sign up to set email alerts
|

Plant Innate Immune Response: Qualitative and Quantitative Resistance

Abstract: Plant diseases, caused by microbes, threaten world food, feed, and bioproduct security. Plant resistance has not been effectively deployed to improve resistance in plants for lack of understanding of biochemical mechanisms and genetic bedrock of resistance. With the advent of genome sequencing, the forward and reverse genetic approaches have enabled deciphering the riddle of resistance. Invading pathogens produce elicitors and effectors that are recognized by the host membrane-localized receptors, which in tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
106
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(109 citation statements)
references
References 164 publications
(145 reference statements)
0
106
0
3
Order By: Relevance
“…An adequate level of resistance that is durable is the most desired characteristic in crop breeding. Quantitative resistance, often governed by several genes, provides durable resistance and hence is recognized by breeders as a valuable approach for protecting crops (Niks et al ., ; Kushalappa et al ., ). In general, two classes of genes govern the genetics of resistance in wheat, race鈥恠pecific resistance ( R ) genes and non鈥恟ace鈥恠pecific resistance genes (that often confer slow鈥恟usting resistance).…”
Section: Historical Perspectives On Wheat Rusts and Resistance Breedimentioning
confidence: 97%
“…An adequate level of resistance that is durable is the most desired characteristic in crop breeding. Quantitative resistance, often governed by several genes, provides durable resistance and hence is recognized by breeders as a valuable approach for protecting crops (Niks et al ., ; Kushalappa et al ., ). In general, two classes of genes govern the genetics of resistance in wheat, race鈥恠pecific resistance ( R ) genes and non鈥恟ace鈥恠pecific resistance genes (that often confer slow鈥恟usting resistance).…”
Section: Historical Perspectives On Wheat Rusts and Resistance Breedimentioning
confidence: 97%
“…Therefore, the quantitative counterpart may have missing components. The missing concept here not necessarily corresponds to complete absence of a particular component, but to differential quantities of resistance related metabolites, proteins coded by R genes, or PRRs, which in turn are regulated by other genes (Kushalappa et al, 2016). Therefore, the more defense-related components are missing (or diminished), the more resistance is reduced.…”
Section: Miscellaneousmentioning
confidence: 99%
“…In this way, resistance known as qualitative could also be polygenic and be achieved if all the components are present and function correctly (Kushalappa et al, 2016). Therefore, the quantitative counterpart may have missing components.…”
Section: Miscellaneousmentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggested that the imbalance of the rhizosphere microecology probably is one important cause for the formation of consecutive monoculture problems in R. glutinosa. Modern plant immunology and molecular biology studies have showed that pathogen infection is closely related to the false response of host plant immune defence system (Smith et al 2014;Kushalappa et al 2016). Previous studies have demonstrated that core biological processes, including DNA replication, RNA transcription and protein translation, are significantly damaged in consecutive monocultures of R. glutinosa.…”
Section: Introductionmentioning
confidence: 99%